The Last Guardian - Luisi, Emelita Rosita Selena Simeaanamulu (My University, 2022)
The Last Guardian is the first in a series of Adult Fantasy Fiction novels that explores the complicated relationships, friendships, social status and belief systems that women of Thäeszar, an empire led by women, must navigate at a pivotal time in history when social unrest gathers momentum and begins to threaten the matriarchal order. It follows the lives of its two main protagonists, the Krīna of Thäeszar Yvainne Yohanna and her myszei, ochKrīna Cecelia Michaela of the Royal House of Zecomb, servants of the old world, its antagonist, an ambitious warrior of the new world, Ser Julius VIII of the noble House of Farrar, and Kathaar, a stable hand with no past. Two powerful Houses are entangled in a fractured history with deep unresolved grievances. The accompanying exegesis The Art of Silence, serves as a guide offering greater insight thematically, to the challenges that Indigenous women face at the hands of incoming colonial patriarchal regimes, and the continued challenges they face within their gender, revealing some confronting truths and possible fallacies that equality for women did not necessarily mean for all women, particularly if one was of Indigenous heritage. Together the exegesis and creative thesis work in tandem to investigate the crises of gender politics, as Western and Indigenous Ideologies collide.